Evaluation of Backfill Operation Models Using SBSC and IFAHP Approach - Yan Li (Advances in Civil Engineering)
As the mine backfill is recognized as one promising technique for the sustainable development, it is crucial to explore the backfill operation mechanism for the mining industry. At present, the self-management and outsourcing model are generally selected to apply in backfill operation and management worldwide. The advantages are insufficient from the strategic and sustainable perspective. Therefore, the study proposes joint venture alliance and concerns the superiority on mine backfill management. In order to evaluate the models, this study puts forward the integrated method which involves combination of SBSC and IFAHP. A strategic and hierarchical framework of SBSC on the basis of sustainability is formulated, which includes 6 perspectives and 16 secondary indexes. Simultaneously, the IFAHP approach is used for determination of the weights of indexes and calculation of the final score, which enables to assess mine backfill operation activity more objectively. The results show that the self-management model provides little advantages whereas the outsourcing model is the better operation mechanism. By contrast, joint venture alliance is rated as the optimal backfill operation model of the mining industry. The research findings of this study would help the mining industry to evaluate objectively and make an appropriate decision on the backfill operation model in the mining industry.